Religion Unbundled: Toward a Twenty-First-Century Paradigm for the Sociology of American Religion - Braunstein, Ruth; Kucinskas, Jaime; Steensland, Brian; Winchester, Daniel (American Sociological Review, 2026)
Much recent sociological work on religion in the United States is written outside the field’s two established paradigms: secularization theory and the 1990s “religious economy” approach. Drawing together strands of recent theoretical innovation and contemporary religious developments that challenge the existing paradigms, we introduce elements of a twenty-first-century paradigm for the sociology of American religion. We argue that the shape-shifting nature of American religion (and secularity) can be productively conceptualized as an effect of unbundling—that is, a process by which religious goods once offered as a package by institutionalized religious authorities are now offered individually or repackaged into various hybrid and contested forms by a wide array of suppliers. We demonstrate the value of our approach by showing how two major religious traditions, Christianity and Buddhism, have become unbundled. In both cases, our approach positions us to apprehend a range of phenomena beyond traditional organized religion, as well as how organized religion adapts to fit this new de facto unbundled landscape. We offer criteria for delimiting the scope of this broader unbundled religious landscape, and discuss the implications of our approach for scholarship on religion, meaning making, and social change.